2009
DOI: 10.1007/s00205-009-0271-4
|View full text |Cite
|
Sign up to set email alerts
|

Invertibility and Weak Continuity of the Determinant for the Modelling of Cavitation and Fracture in Nonlinear Elasticity

Abstract: In this paper we present and analyze a variational model in nonlinear elasticity that allows for cavitation and fracture. The main idea to unify the theories of cavitation and fracture is to regard both cavities and cracks as phenomena of creation of new surface. Accordingly, we define a functional that measures the area of the created surface. This functional has relationships with the theory of Cartesian currents. We show that the boundedness of that functional implies the sequential weak continuity of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
109
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 35 publications
5
109
0
Order By: Relevance
“…Therefore, there exists a minimizing sequence det Dū j > 0 almost everywhere,ū j is one-to-one almost everywhere and E (ū j ) = 786 0 for all j ∈ N, the same proof of [8,Th. 4] shows that there existsū…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Therefore, there exists a minimizing sequence det Dū j > 0 almost everywhere,ū j is one-to-one almost everywhere and E (ū j ) = 786 0 for all j ∈ N, the same proof of [8,Th. 4] shows that there existsū…”
mentioning
confidence: 68%
“…To be precise, Henao and Mora-Corral 60 [8][9][10] showed that when the functional setting allows for cavitation and fracture,…”
mentioning
confidence: 99%
“…[BM84] for such examples, [HMC10] for examples in the context of cavitation and the work in [KKK12] on the weak continuity of null Lagrangians at the boundary. In particular, let p < d, q ≥ p and u ∈ W 1,q (Ω; R d ) such that det ∇u(x) < 0 a.e.…”
Section: Strictly Orientation-preserving Generating Sequencesmentioning
confidence: 99%
“…A number of micromechanical and computational models, ranging from atomistic to continuum, have been put forth (cf., e. g., Leonov and Brown (1991); Krupenkin and Fredrickson (1999a,b); Tijssens et al (2000a,b); Estevez et al (2000a,b); Baljon and Robbins (2001); Socrate et al (2001); Drozdov (2001); Tijssens and van der Giessen (2002); Robbins (2003, 2004); Basu et al (2005); Saad-Gouider et al (2006); Zairi et al (2008); Seelig and Van der Giessen (2009) ;Reina et al (2013)), including consideration of nucleation and growth Figure 2: Crazing process in a steel/polyurea/steel sandwich specimen under opening mode fracture (Yong et al, 2009). of voids, craze nucleation, network hardening and disentanglement, chain strength, surface energy and other, that account, to varying degrees, for the observational evidence and relate macroscopic properties to material structure and behavior at the microscale. In parallel a large mathematical literature has evolved, discussing the possibility of cavitation in local models and possible nonlocal extensions which may ensure existence of minimizers, see for example Ball (1982); James and Spector (1991); Müller and Spector (1995); Conti and DeLellis (2003); Henao and Mora-Corral (2010). These advances notwithstanding, the connection between micromechanical properties and polymer fracture, and specifically any scaling laws thereof, has defied rigorous analytical treatment and characterization.…”
Section: Introductionmentioning
confidence: 99%